Validity and Reliability Analysis: Measuring the Accuracy and Consistency of Instruments for the Evaluation of Islamic Religious Education Tests (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Accurate and consistent measurement instruments are indispensable for conducting evaluations. Without adequate validity and reliability, PAI test results can be inaccurate and unreliable, thus obscuring the purpose of the evaluation. This study aims to analyze the importance of validity and reliability in the development of effective PAI tests. The method used is a literature study, by collecting and reviewing various sources such as books and relevant journal articles, which are then critically analyzed. The results of the analysis show that the fulfillment of validity, both from the content and construct aspects, as well as the consistency of results through high reliability, is very important to ensure that the test is truly accurate and reliable to be a measuring tool for the achievement of learning objectives. This study is expected to provide insight for PAI test instrument developers in creating more credible evaluation tools, in order to support a better and more meaningful religious learning process.